THE INFLUENCE OF MICROWAVE HEATING AND ANTIOXIDANTS ON THE OXIDATIVE STABILITY OF COLD-PRESSED VEGETABLE OILS - Begić, Munevera; Hrustanović, Mithat; Kavazović, Nejra; Slijepčević, Amila; Đinović Stojanović, Jasna; Čorbo, Selma (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Lipid oxidation is a significant problem in the production, processing and use of edible oils, which causes significant changes in chemical, sensory and nutritional properties. Therefore, the aim of this research was to examine the influence of microwave heating and antioxidants, natural and synthetic, on the oxidative stability of cold-pressed vegetable oils (rapeseed oil, sesame oil and milk thistle seed oil). Cumin and fennel essential oils were used as natural antioxidants, and propyl gallate (PG) and butylhydroxytoluene (BHT) as synthetic antioxidants. The test was carried out by determining the value of the peroxide value in the tested samples, first through the impact of microwave heating of different intensity at the same sampling time, as well as microwave heating of the same intensity sampled every 5 minutes up to a maximum of 25 minutes. By extending the time of microwave heating at constant power (140 W), the values of peroxide value increased in all tested samples with and without the addition of antioxidants. The biggest changes in the value of the peroxide value were recorded in milk thistle seed and rapeseed oil, and the least in sesame oil. The best protection against oxidative deterioration was seen in BHT in all tested samples, as well as in fennel essential oil in rapeseed oil. With the increase of the power intensity of the device during microwave heating for the duration of 5 minutes, the values of the peroxide value of all tested samples increased, both with and without the addition of antioxidants. Using different powers of microwave heating (140 W, 280 W and 420 W), the best protection against oxidative deterioration of sesame oil was shown by PG, milk thistle seed oil by BHT and PG, and rapeseed oil by fennel essential oil and BHT.